Dissection of familial correlations in hepatitis C virus (HCV) seroprevalence suggests intrafamilial viral transmission and genetic predisposition to infection. Issue 9 (14th May 2008) - Plancoulaine, S; Mohamed, M K; Arafa, N; Bakr, I; Rekacewicz, C; Trégouët, D-A; Obach, D; El Daly, M; Thiers, V; Féray, C; Abdel-Hamid, M; Abel, L; et al.
Abstract : Objective: Unsafe injections and transfusions used during treatments are considered to be responsible for many cases of transmission of hepatitis C virus (HCV) in developing countries, but cannot account for a substantial proportion of present infections. The aim of the present work was to investigate familial clustering of HCV infection in a population living in a highly endemic area. Design, setting and participants: A large seroepidemiological survey was conducted on 3994 subjects (age range, 2–88 years) from 475 familial clusters in an Egyptian rural area. Epidemiological methods appropriate for the analysis of correlated data were used to estimate risk factors and familial dependences for HCV infection. A phylogenetic analysis was conducted to investigate HCV strain similarities within and among families. Main outcome measures: HCV familial correlations adjusted for known risk factors, similarities between viral strains. Results: Overall HCV seroprevalence was 12.3%, increasing with age. After adjustment for relevant risk factors, highly significant intrafamilial resemblances in HCV seroprevalence were obtained between father–offspring (odds ratio (OR) = 3.4 (95% confidence interval (CI), 1.8 to 6.2)), mother–offspring (OR = 3.8 (95% CI, 2.5 to 5.8)), and sibling–sibling (OR = 9.3 (95% CI, 4.9 to 17.6)), while a weaker dependence between spouses (OR = 2.2 (95% CI, 1.3 to 3.7)) was observed. Phylogenetic analysis showed greater HCV strain similarity between family members than between unrelated subjects, indicating that correlations can be explained, in part, by familial sources of virus transmission. In addition, refined dissection of correlations between first-degree relatives supported the role of host genes predisposing to HCV infection. Conclusions: Current HCV infection in endemic countries has a strong familial component explained, at least partly, by specific modes of intrafamilial viral transmission and by genetic predisposition to infection.